2018
DOI: 10.1016/j.memsci.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive condensation flow regimes in air gap membrane distillation: Visualization and energy efficiency

Abstract: The thermal performance of air gap membrane distillation (AGMD) desalination is dominated by heat and mass transfer across the air gap between the membrane and the condensing surface. However, little is known about the impact of condensate flow patterns in some design variations of the air gap. In this study, air gap membrane distillation experiments were performed at various inlet temperatures, varying module inclination angle, condensing surface hydrophobicity, and gap spacer design to identify the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…On the other hand, membrane distillation utilizes thermal energy to provide the driving pressure force, which does not deteriorate significantly for high salinity feed [9][10][11][12][13][14][15]. Additionally, supplementing the membrane distillation (MD) module with a vacuum pump on the distillate side, commonly known as vacuum membrane distillation (VMD), further improves the performance for extremely high salinity feed [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, membrane distillation utilizes thermal energy to provide the driving pressure force, which does not deteriorate significantly for high salinity feed [9][10][11][12][13][14][15]. Additionally, supplementing the membrane distillation (MD) module with a vacuum pump on the distillate side, commonly known as vacuum membrane distillation (VMD), further improves the performance for extremely high salinity feed [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Warsinger et al [42] investigation on condensation flow regimes in AGMD suggested that flooding and trapping of droplets would be minimized in case of lower AGMD fluxes. These results are well correlated with our observations when a significant increase in vapor flux achieved at high feed temperatures at n = 3 was decreaded when the number of condenser fibers n was further increased to 4.…”
Section: Effect Of Feed Temperature and Number Of Condenser Fibers On Water Vapor Fluxmentioning
confidence: 94%
“…As such, there would exist an optimal number of condenser fibers which would facilitate high condensation area while maintaining small mass transfer resistance. The lower condensate removal rate compared to permeate production rate would cause permeate flooding inside the AGMD module as it has been recently addressed in a number of studies [42][43][44][45]. Despite the improved permeate flux, the thermal efficiency of the process is decreased due to the air replacing water which has poorer insulating properties [42].…”
Section: Effect Of Feed Temperature and Number Of Condenser Fibers On Water Vapor Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors that limit its applications in industrial fields are scale and stability, similar to many emerging technologies. The majority of the studies on MD are focused on the development of novel porous membranes for MD applications [8][9][10][11][12], the transmembrane transport analysis in microscale [13][14][15][16][17], the configurations and their related performance [18][19][20]. The MD performance criteria usually include the permeate flux, salt rejection, specific energy consumption, scaling resistance and operating stability.…”
Section: Introductionmentioning
confidence: 99%